Pengaruh Insentif terhadap Kinerja Pegawai pada Dinas Pendidikan Tanjung Jabung Timur - Monica Sari (Science of Management and Students Research Journal (SMS), 2021)
This study aims to determine the effect of incentives on employee performance at the Tanjung Jabung Timur Education Office. In this study, the research population is all employees of the Tanjung Jabung Timur Education Office in 2021 with a total of 42 civil servants. The analytical tool used in this research is a scale range, instrument assumption test which consists of validity and reliability test, simple linear regression, correlation coefficient and determination, and t test. Data processing using SPSS 25.00 software. Before testing the hypothesis, the instrument's assumption test was conducted. The results of the instrument assumption test consisting of validity and reliability tests indicate that the data has met the requirements.  Based on the simple linear regression equation, Y = 0.356 + 0.831.X + e. This means that the Incentive variable affects the performance of 0.831 or 83.1%. And in the hypothesis test, tcount for incentives is greater than ttable (5.844 > 2.02108). On the other hand, the significant value is less than 0.05, namely 0.000 <0.05, and the regression coefficient value of the Incentive (X) is marked (+). The results of hypothesis testing indicate that incentives have a significant effect on employee performance at the Tanjung Jabung Timur Education Office.